Shape Memory Polymer Microstructures Using Melt Electrowriting - Biranche Tandon; Nasim Sabahi; Reza Farsi; Taavet Kangur; Xiaopeng Li; Jürgen Brugger (Proceedings)
Melt electrowriting is a relatively new additive manufacturing technique capable of the controlled deposition of polymeric fibers to manufacture pre-programmed structures at micron scale. In this research, a blend of poly (ε-caprolactone) and thermoplastic urethane displaying shape memory properties is processed using melt electrowriting. The bulk material at macro scale shows a transition temperature of around 60 °C. Fibers with diameter less than 60 µm were deposited as sinusoids and grid-like scaffolds. A high strain fixity ratio of 92% was obtained for the polymer, which is in accordance with the literature on shape memory polymers. These shape memory structures can be used for applications such as micro-sensing and actuating.